NarAB Is an ABC-Type Transporter That Confers Resistance to the Polyether Ionophores Narasin, Salinomycin, and Maduramicin, but Not Monensin - Naemi, Ali-Oddin; Dey, Hymonti; Kiran, Nosheen; Sandvik, Sarah Torbergsen; Slettemeås, Jannice Schau; Nesse, Live L.; Simm, Roger (Frontiers in Microbiology, 2020)
Polyether ionophores are antimicrobial compounds used as feed additives in poultry feed to control diseases caused by coccidia. In addition to the anticoccidial activity of these compounds, polyether ionophores also have antibacterial effect. Resistance to the polyether ionophore narasin was recently shown to exist on mobile plasmids in Enterococcus faecium and the resistance mechanism was suggested to be associated with a two-gene operon encoding an ABC-type transporter. In this study we demonstrate that the genes encoding the putative narasin resistance mechanism confers reduced susceptibility to the polyether ionophores narasin, salinomycin and maduramicin, but not to monensin and suggest that this resistance mechanism should be referred to as NarAB. Importantly, NarAB does not affect the susceptibility of Enterococcus faecium to any of the tested antimicrobial compounds that are used in clinical medicine. However, we show that certain polyether ionophores stimulate the number of vancomycin resistant Enterococcus faecium during conjugation of a plasmid encoding both narasin-resistance and vancomycin-resistance. This suggests that narasin and certain other polyether ionophores can contribute to the persistence of VRE in poultry populations.